Systemic inflammatory markers and oncologic outcomes in patients with high-risk non-muscle-invasive urothelial bladder cancer - Cantiello, Francesco (2018)
Serum levels of neutrophils, platelets, and lymphocytes have been recognized as factors related to poor prognosis for many solid tumors, including bladder cancer (BC). Background Serum levels of neutrophils, platelets, and lymphocytes have been recognized as factors related to poor prognosis for many solid tumors, including bladder cancer (BC). Objective To evaluate the prognostic role of the combination of the neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), and lymphocyte/monocyte ratio (LMR) in patients with high-risk non–muscle-invasive urothelial BC (NIMBC). Design, setting, and participants A total of 1151 NMIBC patients who underwent first transurethral resection of the bladder tumor (TURBT) at 13 academic institutions between January 1, 2002 and December 31, 2012 were included in this analysis. The median follow-up was 48 mo. Intervention TURBT with intravesical chemotherapy or immunotherapy. Outcome measurements and statistical analysis Multivariable Cox regression analysis was performed to identify factors predictive of recurrence, progression, cancer-specific mortality, and overall mortality. A systemic inflammatory marker (SIM) score was calculated based on cutoffs for NLR, PLR, and LMR. Results and limitations The 48-mo recurrence-free survival was 80.8%, 47.35%, 20.67%, and 17.06% for patients with an SIM score of 0, 1, 2, and 3, respectively (p < 0.01, log-rank test) while the corresponding 48-mo progression free-survival was 92.0%, 75.67%, 72.85%, and 63.1% (p < 0.01, log-rank test). SIM scores of 1, 2, and 3 were associated with recurrence (hazard ratio [HR] 3.73, 7.06, and 7.88) and progression (HR 3.15, 4.41, and 5.83). Limitations include the lack of external validation and comparison to other clinical risk models. Conclusions Patients with high-grade T1 stage NMIBC with high SIM scores have worse oncologic outcomes in terms of recurrence and progression. Further studies should be conducted to stratify patients according to SIM scores to identify individuals who might benefit from early cystectomy. Patient summary In this study, we defined a risk score (the SIM score) based on the measurement of routine systemic inflammatory markers. This score can identify patients with high-grade bladder cancer not invading the muscular layer who are more likely to suffer from tumor recurrence and progression. Therefore, the score could be used to select patients who might benefit from early bladder removal.